“Education Changes the World”: The World University Service of Canada’s Student Refugee Program - Peterson, Glen (Refuge: Canada’s Journal on Refugees, 2012)
This paper reflects on the origins and development of the Student Refugee Program of the World University Service of Canada (WUSC) and its significance as a “transformational” force in the lives of individuals and communities. The WUSC Student Refugee Program is a unique effort involving students, faculty and staff at universities and colleges across Canada who work together to mobilize material and human resources in order to enable student refugees to resettle and complete their post-secondary studies in Canada. The author, who has worked closely with the Student Refugee Program at the University of British Columbia since the mid-1990s, first describes the operation of the Student Refugee Program, and then considers its significance in relation to issues of resettlement, gender equality, “brain drain” and transnationalism.